Varsities retain research status - The Sun, (2010)
Universiti Malaya, Universiti Kebangsaan Malaysia, Universiti Sains Malaysia and universiti Putra Malaysia have retained their status as research universities for another three years begining this year, Higher Education Minister Datuk Seri Mohamed Khalid Nordin said yesterday.